Design and Development of In-Line Optical Amplifiers - Syed Ibrahim, Sharifah Noriza (2004)
Fiber optic technology is not entirely perfect, even with its amazing capabilities. As the transmissions cover larger distances, signal loss occurs and amplification is required. Hence, to transmit information over longer distances, the optical signals need to be boosted. The conventional method of boosting these signals is by using the electrical repeaters. The concept of electrical repeaters may sound attractive, but it poses several problems. This is because repeaters can only work at specific bit rate, wavelength and modulation format. The need for optical amplifiers has arisen because the repeaters concept delays the transmission and may introduce noise in the signal. Optical signals require amplification at different points on communications links. There are three types of amplifiers located along this link. The first type is the power amplifiers that are placed directly after the optical transmitter. Secondly, there are the in-line amplifiers that operate with a signal in the middle of a fiber-optic link and lastly, the pre amplifiers, which magnify the signal before it reaches the receiver. In this research, the design and development of optical amplifiers focused only on in-line amplifiers. Among the variety of optical amplifiers, Erbium doped fiber amplifiers were chosen as the optical amplifiers because erbium is the most efficient active medium that allows optical signals to be transmitted over very long distances without the need for signal regeneration. In this thesis, the hands-on experiments of the in-line optical amplifiers design were carried out. The design models comprised single and double stages of Erbium doped fiber amplifiers setups. At the single stage device level, testing was conducted to study the effects of the design parameters that are pump power, Erbium doped fiber length, signal wavelength and input power. The analysis on the double stage Erbium doped fiber amplifier was carried out for the device level testing based on the effects of the performance parameters i.e., gain, output power, noise figure and Amplified Spontaneous Emission level with the inclusion of tunable band pass filter. The results showed that the double stage amplifiers had a greater advantage compared to the single stage. The double stage Erbium doped fiber amplifiers with tunable band pass filter and the utilization of the backward pumping scheme had increased the gain more than that with the forward pumping scheme. The noise problem created in the Erbium doped fiber amplifiers was the main source that contributed to the high Amplified Spontaneous Emission. The concatenated chain caused the Amplified Spontaneous Emission to accumulate. Hence, inserting a tunable band pass filter in the design reduced the noise figure. Varying the parameters and selecting the suitable setup can improve the performance of the in-line amplifier system. The results of the study showed the most suitable design setup is the double stage Erbium doped fiber amplifiers, which increase the gain but reduce the noise level